Control of growth and organ size in Drosophila. - Johnston, L.A.; Gallant, P. (BioEssays, 2002)
Transplantation experiments have shown that developing metazoan organs carry intrinsic information about their size and shape. Organ and body size are also sensitive to extrinsic cues provided by the environment, such as the availability of nutrients. The genetic and molecular pathways that contribute to animal size and shape are numerous, yet how they cooperate to control growth is mysterious. The recent identification and characterization of several mutations affecting growth in Drosophila melanogaster promises to provide insights. Many of these mutations affect the extrinsic control of animal size; others affect the organ-intrinsic control of pattern and size. In this review, we summarize the characteristics of some of these mutations and their roles in growth and size control. In addition, we speculate about possible connections between the extrinsic and intrinsic pathways controlling growth and pattern.